2021
DOI: 10.1111/anu.13231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type of dietary non‐protein energy source (starch vs. fat) on the body bile acid pool size and composition, faecal bile acid loss and bile acid synthesis in rainbow trout (Oncorhynchusmykiss)

Abstract: Effects of the type of dietary non‐protein energy source on the size and composition of the total body bile acid pool, on faecal bile acid loss and on bile acid synthesis were investigated in rainbow trout. Two diets were formulated (similar DP:DE ratio) that differed in the inclusion of either maize starch (Starch) or rapeseed oil (Fat) as main non‐protein source. Fish were fed to satiation for 44 days. Type of non‐protein energy source did not substantially affect the body bile acid pool composition. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 75 publications
(130 reference statements)
1
3
0
Order By: Relevance
“…The BA family in animals is quite complex. Similar to the reports on the human [34], mice [35], and rainbow trout [36], we also found that the common carp can conjugate bile acid with glycine, but not only with taurine. In some early views, it was pointed out that animals, except for the mammals, conjugate their BAs exclusively with taurine [37,38], which led to the fact that less attention was paid to G-BAs when studying fish bile acids.…”
Section: Ba Profile Changes Caused By Supplements Of Bassupporting
confidence: 90%
See 1 more Smart Citation
“…The BA family in animals is quite complex. Similar to the reports on the human [34], mice [35], and rainbow trout [36], we also found that the common carp can conjugate bile acid with glycine, but not only with taurine. In some early views, it was pointed out that animals, except for the mammals, conjugate their BAs exclusively with taurine [37,38], which led to the fact that less attention was paid to G-BAs when studying fish bile acids.…”
Section: Ba Profile Changes Caused By Supplements Of Bassupporting
confidence: 90%
“…However, the fish meal in the experimental diets of this study only accounted for 10%, which made the bile acids level in the basal diet lower than the detection limit of LC-MS/MS. In the study of Staessen et al (2021) [36], 27% fishmeal and 1.3% fish oil were used and about 1.1 × 10 −5 umol/mg GBA were detected in the basal diet. In the present study, the dietary bile acid profile was composed with HCA (8.0%), HDCA (70.9%), and CDCA (20.2%), and the two experimental diets were designed with the same level of fishmeal.…”
Section: Ba Profile Changes Caused By Supplements Of Basmentioning
confidence: 99%
“…The protein content of the liver was determined using a kit produced by Beyotime Biotechnology Co., Ltd. (Shanghai, China). The lipids in the liver were extracted and determined in accordance with the method reported by Staessen et al [ 22 ]. The collagen fibre content in the liver was determined with Fish COL ELISA Kit (Sanjia, China).…”
Section: Methodsmentioning
confidence: 99%
“…The fetus grows fast during late gestation indicating an active exchange of nutrients between the fetus and placenta [1]. Fat and starch are common sources of energy in diets, although starch possesses a lower caloric density than fat [2]. To satisfy the rapid growth of the fetus, sows undergo many physiological changes [3], such as an increased circulating concentration of hormones [4].…”
Section: Introductionmentioning
confidence: 99%